Pengaruh Kepemilikan Institusional, Corporate Social Responsibility,Ukuran Perusahaan dan Investment Opportunity Set terhadap Nilai Perusahaan - Alfa Mariana Bleszyski; Purwanto Purwanto; Sari Widati (Journal Of Business, Finance, and Economics (JBFE), 2022)
This research aims to test the effect of institusional ownwership, corporate social responsibility, firm size and investment opportunity set to firm value of non financial company that listed at Indonesia Stock Exchange in 2015-2018. The sample used in the study is 151 observations of non financial companies listed on the Indonesia Stock Exchange in the period 2015 to 2018 and took a sample using purposive sampling method. The data in the study came from the secondary data obtained through technical documentation. Data analysis technique used is the classial assumption test and multiple regression with the help of SPSS 21 for windows. The data of this study was to quality the classical assumption and test the suitability of the model with an adhusted R2 of 60,3%. The results show that: institusional ownership and firm size has a no effect to corporate value; corporate social responsibility and investment opportunity set has a positive significant to corporate value.Keyword : institusional ownership, corporate social responsibility, firm size, investment opportunity set, firm value